The Nostalgic Negotiation of Post-TV Legibility in Mom, Don’t Do That! - Eunice Ying Ci Lim (Global Storytelling)
The success and legibility of South Korean Netflix dramas like Squid Game (2021) have reinforced the position of Korean television dramas (K-dramas) at the forefront of both Asian and global entertainment. As one of the major consumers of Korean Wave products, Taiwan’s entertainment industry necessarily situates itself regionally, transnationally, and globally in relation to and in response to K-dramas’ dominance. The recently released Taiwanese Netflix television series Mom, Don’t Do That! (媽,別鬧了!, 2022) is a key development in Global Taiwanese television drama that reflects on and responds to the unabating Korean Wave (Hallyu or K-Wave) and the regional and global popularity of K-dramas on Netflix and other post-television over-the-top (OTT) media-viewing platforms. By alluding to the genre conventions that characterize Taiwanese prime time Hokkien dialect (Minnan) dramas and Taiwanese Mandarin idol-dramas, Mom Don’t Do That! (MDDT) strategically encourages a transnational nostalgia toward a golden era of Taiwanese dramas. This nostalgia, in turn, strategically allows MDDT to negotiate a new position for global Taiwanese television drama, challenging K-dramas’ ubiquity and Netflix’s curative influence on global media-consumption cultures. MDDT self-reflexively stages the domestic obsolescence of television, juxtaposes their screen-mediated food-consumption practices with the mediated foodways that have come to characterize the K-Wave, and highlights the unlikely and unhealthy nature of K-drama’s romantic tropes and archetypes. These strategic moves variously establish MDDT as a sustained metacommentary on the K-drama-dominated, post-TV conditions that continue to shape media-viewing practices and cultures of today.